Knowledge Relationships in Freshwater Governance - A. Amu-Mensah Marian; B. Kendie Stephen; K. Amu-Mensah Frederick; K. Barima Antwi; Farhad Analoui; O. Mireku Dickson; B. Amu-Mensah Saraphina (New Ideas Concerning Science and Technology Vol. 7, 2021)
Freshwater governance policy formulation and implementation are usually undertaken with little consideration to the thought processes generated from the local communities around the resource environment, thus emphasising a top-down approach to water governance. Even though considerable efforts have been made to the social change theory by incorporating stakeholders’ views, the individual-level or local-level insights, as well as constructs and environmental connections (cognitive view) in freshwater challenges, are usually left out. Using the case study research design, with emphasis on the descriptive design helped to access local knowledge in freshwater governance. The mixed-method approach helped to put together information based on behavioural concerns, the spirituality of the people, and the resource environmental concerns needed for the analysis and discussion of the data while drawing a meaningful conclusion from the data. The results provide a framework, which will help to address interventions that simultaneously cover both development and behavioural determinants of freshwater degradation, toward social change conservation policy in reducing crisis in freshwater governance.